HX‐MS2 for high performance conformational analysis of complex protein states. (29th May 2015) - Burns, Kyle M.; Sarpe, Vladimir; Wagenbach, Mike; Wordeman, Linda; Schriemer, David C.
Abstract Water‐mediated hydrogen exchange (HX) processes involving the protein main chain are sensitive to structural dynamics and molecular interactions. Measuring deuterium uptake in amide bonds provides information on conformational states, structural transitions and binding events. Increasingly, deuterium levels are measured by mass spectrometry (MS) from proteolytically generated peptide fragments of large molecular systems. However, this bottom‐up method has limited spectral capacity and requires a burdensome manual validation exercise, both of which restrict analysis of protein systems to generally less than 150 kDa. In this study, we present a bottom‐up HX‐MS2 method that improves peptide identification rates, localizes high‐quality HX data and simplifies validation. The method combines a new peptide scoring algorithm (WUF, weighted unique fragment) with data‐independent acquisition of peptide fragmentation data. Scoring incorporates the validation process and emphasizes identification accuracy. The HX‐MS2 method is illustrated using data from a conformational analysis of microtubules treated with dimeric kinesin MCAK. When compared to a conventional Mascot‐driven HX‐MS method, HX‐MS2 produces two‐fold higher α/β‐tubulin sequence depth at a peptide utilization rate of 74%. A Mascot approach delivers a utilization rate of 44%. The WUF score can be constrained by false utilization rate (FUR) calculations to return utilization values exceeding 90% without serious data loss, indicating that automated validation should be possible. The HX‐MS2 data confirm that N‐terminal MCAK domains anchor kinesin force generation in kinesin‐mediated depolymerization, while the C‐terminal tails regulate MCAK‐tubulin interactions.